Primary hepatic neuroendocrine carcinoma diagnosed by needle biopsy: a case report - Yusuke Seki (SpringerOpen, 2021)
Abstract Background Primary hepatic neuroendocrine carcinomas (NECs) are extremely rare. The rate of recurrence after resection is extremely high, and the prognosis is poor. It is debatable whether chemotherapy or surgical resection is the optimal initial treatment for primary hepatic NECs. Therefore, selecting an appropriate therapeutic approach for patients with primary hepatic NECs remains clinically challenging. We present a case of primary hepatic NEC in a patient who developed recurrence after undergoing surgical resection. Case presentation A 78-year-old man with bone metastases of prostate cancer was referred to our department because of a solitary 66-mm tumor in the left lateral segment of the liver, which was detected on annual follow-up by computed tomography after prostate resection. A biopsy and preoperative diagnostic workup identified the lesion as a primary hepatic neuroendocrine carcinoma; therefore, left lateral segmentectomy was performed. Immunohistochemically, the tumor was positive for chromogranin A, synaptophysin, and CD 56, and the Ki-67 index was 40%. This neuroendocrine carcinoma was classified as a large cell type. Adjuvant chemotherapy with carboplatin + etoposide was initially administered a month after surgery. However, lymph node recurrence occurred 4 months after surgery, and the patient died of systemic metastases 15 months after surgical resection. Conclusions Due to the lack of availability of abundant quantities of relevant, high-quality data, there is no standard therapy for primary hepatic NECs. Selecting the most appropriate treatment for patients depending on several factors, such as the stage and differentiation of a tumor and a patient’s performance status and clinical course, is consequently preferred. More cases need to be studied to establish the best treatment strategy for primary hepatic NEC.